2016
DOI: 10.1016/j.crci.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Recent progress in catalytic NO decomposition

Abstract: a b s t r a c tRecent progress in catalytic direct NO decomposition is overviewed, focusing on metal oxide-based catalysts. Since the discovery of the Cu-ZSM-5 catalyst in the early 1990s, various kinds of catalytic materials such as perovskites, C-type cubic rare earth oxides, and alkaline earth based oxides have been reported to effectively catalyze direct NO decomposition. Although the activities of conventional catalysts are poor in the presence of coexisting O 2 and CO 2 , some of the catalysts reviewed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 93 publications
2
36
0
1
Order By: Relevance
“…Haneda [22,58] proposed that over alkali metal doped Co 3 O 4 catalysts, NO 2 − species probably react with another NO adspecies resulting in the formation of N 2 O x intermediates, which decompose very fast into gaseous N 2 and adsorbed oxygen species. In the literature, it was most often considered that oxygen desorption is the rate determining step; however, some other steps like the attack of second NO molecule on the oxygen vacancy, NO 2 formation, N 2 O formation and decomposition were also considered by different authors [59,60]. Anyway, the suggestion that the formation of N 2 is directly caused from the collision of two activated nitrogen atoms and that formation of O 2 is combined by the two adsorbed oxygen atoms is valid across a lot of different studies [60].…”
Section: Discussionmentioning
confidence: 99%
“…Haneda [22,58] proposed that over alkali metal doped Co 3 O 4 catalysts, NO 2 − species probably react with another NO adspecies resulting in the formation of N 2 O x intermediates, which decompose very fast into gaseous N 2 and adsorbed oxygen species. In the literature, it was most often considered that oxygen desorption is the rate determining step; however, some other steps like the attack of second NO molecule on the oxygen vacancy, NO 2 formation, N 2 O formation and decomposition were also considered by different authors [59,60]. Anyway, the suggestion that the formation of N 2 is directly caused from the collision of two activated nitrogen atoms and that formation of O 2 is combined by the two adsorbed oxygen atoms is valid across a lot of different studies [60].…”
Section: Discussionmentioning
confidence: 99%
“…The direct decomposition of nitric oxide has been studied and described in some publications [6]. Apart from metals (Pt, Pd, Ag, Rh, Ni, Cu, Mo, Co, Au), metal oxides like Co 3 O 4 , Fe 2 O 3 , NiO, CuO, and ZrO 2 ; lanthanides; perovskites; and mixed oxides were also studied for direct NO decomposition [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen oxides (NOx) formed by combustion from fixed and mobile sources cause severe detrimental environmental problems, such as acid rain and photochemical smog [1][2][3]. Effectively controlling the emission of NOx is the topic of much research and has led to the introduction of many new catalyst technologies, such as three-way catalysts (TWC), NOx storage-reduction (NSR), and selective catalytic reduction (SCR) for NOx gas removal from mobile sources, and SCR and selective non-catalytic reduction (SNCR) for NOx gas removal from fixed sources [4][5][6]. Among various deNOx strategies, direct decomposition of NO (NO→1/2O 2 + 1/2N 2 ) has been considered to be the most desirable method because this reaction is thermodynamically favorable at low temperatures and does not need any reductants, such as NH 3 , H 2 , CO, or hydrocarbons.…”
Section: Introductionmentioning
confidence: 99%
“…Among various deNOx strategies, direct decomposition of NO (NO→1/2O 2 + 1/2N 2 ) has been considered to be the most desirable method because this reaction is thermodynamically favorable at low temperatures and does not need any reductants, such as NH 3 , H 2 , CO, or hydrocarbons. However, kinetic studies have indicated that the reaction needs to overcome a large activation energy (~335 kJ mol −1 ) barrier [4][5][6][7][8][9][10][11][12][13][14][15]. Accordingly, there is an apparent need for a suitable catalyst to decompose NOx at a given temperature, and therefore, significant research has been undertaken towards development of active and stable catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation